2010
DOI: 10.1063/1.3463457
|View full text |Cite
|
Sign up to set email alerts
|

Silicon oxide based n-doped layer for improved performance of thin film silicon solar cells

Abstract: We propose the use of n-doped silicon oxide as alternative n-layer in thin film Si p-i-n solar cells. By varying input gas ratios, films with a wide range of optical and electrical properties are obtained. Applying these layers in solar cells, good electrical and optical properties are demonstrated. A relative efficiency increase up to 13.6% has been observed on the cells adopting a simple Ag back contact. A similar spectral response as with the cell with standard n-layer plus ZnO/Ag back contact is obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 11 publications
4
23
0
Order By: Relevance
“…When doped silicon oxide was used as n‐layer, the current of the bottom cell strongly increased going from 10.6 to 12.3 mA/cm 2 , whereas a practically identical spectral response was obtained for the top cells ( J SC = 10.6 mA/cm 2 ). As recently suggested in the literature for single junctions , optical and electrical effects could act simultaneously at improving the device performance. However, in this case, because the devices showed similar electrical parameters, the optical properties of the alternative n‐layers should be mainly responsible for the observed effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When doped silicon oxide was used as n‐layer, the current of the bottom cell strongly increased going from 10.6 to 12.3 mA/cm 2 , whereas a practically identical spectral response was obtained for the top cells ( J SC = 10.6 mA/cm 2 ). As recently suggested in the literature for single junctions , optical and electrical effects could act simultaneously at improving the device performance. However, in this case, because the devices showed similar electrical parameters, the optical properties of the alternative n‐layers should be mainly responsible for the observed effects.…”
Section: Resultsmentioning
confidence: 99%
“…This material has been widely investigated as intermediate reflector layer in micromorph tandem solar cells , as window layer in n‐side illuminated microcrystalline silicon n–i–p solar cells , and as a thin resistive extra layer between the p–i–n solar cell and the back contact to improve the electrical properties by quenching undesired current drains . Recently, very promising results have also been obtained in adopting n‐doped silicon oxide as alternative n‐layer in single junction p–i–n a‐Si:H solar cells: in this case, with a single‐layer metal back contact, the devices have shown similar or even better performance with respect to cells fabricated using standard microcrystalline silicon n‐layer with ZnO/Ag back reflector . In the present work, we intent to extend these results to tandem micromorph solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The individual contributions of these two phases provide a straightforward way to tune the optoelectronic properties of nc-SiO X :H. However, during the PECVD deposition of nc-SiO X :H many parameters like pressure, power, frequency and the individual gas flows can be varied, all of which affect the properties of the deposited thin films. Consequently, much research has been devoted to achieve the optimum trade-off between the conductivity and the optical properties of the material [5,[8][9][10] by tuning the deposition conditions. In this paper, we developed a microstructure model based on numerous n-and p-doped nc-SiO X :H films that were deposited under various deposition pressures, plasma powers, plasma frequencies and gas mixtures to provide guidelines for a systematic classification of nc-SiO X :H by establishing a link between the structure of the deposited films and the optoelectronic performance of nc-SiO X :H. This classification helps to identify the structure of the deposited nc-SiO X :H material and provides hints for further optimization steps.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Further applications are n-type window layers in n-i-p microcrystalline silicon (lc-Si:H) solar cells, 8 the replacement of the transparent conductive oxide (TCO) in a conventional TCO/Ag reflector in amorphous silicon (a-Si:H) and lc-Si:H single junction-and in a-Si:H/lc-Si:H tandem-cells. 9,10 Moreover, lc-SiO x :H can be deposited by conventional plasma-enhanced chemical vapor deposition (PECVD) in industrial processes on large area. 2,11 Microcrystalline silicon oxide is a two phase material consisting of lc-Si:H and a-SiO x :H. 12 Energy filtered transmission electron microscopy (EF-TEM) studies have shown recently that the crystalline growth is strongly directional leading to crystalline silicon columns of only a few nanometers in diameter within an a-SiO x :H matrix.…”
mentioning
confidence: 99%